The Effect of Kangaroo Care on Pain Score During Repeated Heel Lance in Newborns - Gülen Yücel; Hatice Yıldırım Sarı; Özgür Olukman (Galenos Publishing House, 2020)
INTRODUCTION: The aim of this study was to investigate the effect of kangaroo care provided during recurrent heel lance procedures on the pain score of a newborn. METHODS: The study is a randomized controlled experimental study. It included 60 2- to 7-day-old term-born newborns hospitalized with the diagnosis of moderate-risk hyperbilirubinemia. Of them, 30 were assigned into the intervention group and 30 to the control group. In the unit where the study was conducted, all newborns having no oral intake problem are administered one or two ml of 25% dextrose solution two minutes before the procedure. The newborns in the control group underwent the clinical routine at each pain interference. The newborns in the intervention group were given a 30-minute kangaroo care before the last pain intervention. Just before the intervention, they were administered 25% sucrose solution orally, a routine procedure in the clinic. Heel lance was performed by the researcher using the appropriate technique. The pain score was assessed by two observers independently of each other using the NIPS scale during and two minutes after the procedure. RESULTS: During the first heel lance procedure, no difference was found between the mean pain scores of the newborns in the intervention and control groups. However, during the second heel lance procedure, the mean pain score of the newborns who received kangaroo care (3.13 +- 2.33) was significantly lower than that of the newborns in the control group (6.10 +- 0.96) (p <0.001). After the second heel lance procedure, the mean pain score was 0.33 +- 1.18 in the newborns who received kangaroo care and 1.07+-2.20 in the newborns in the control group, and the difference was not significant (p>0.05). DISCUSSION AND CONCLUSION: In conclusion, it was found that kangaroo care decreased the pain score during the recurrent heel lance procedures.